Post-stroke diabetes management: a qualitative study - Hewitt, Jonathan; Azhari, Hala F.; O’Neill, Martin; Smith, Alexander; Quinn, Terence; Dawson, Jesse (Frontiers in Neurology, 2024)
Introduction Diabetes is associated with an increased risk of stroke. In many cases, a diabetes diagnosis may predate a stroke; however, diabetes is often diagnosed during the hospital admission following a stroke. To explore the experiences of stroke survivors as they cope with a new diabetes diagnosis, particularly regarding developing an effective strategy for managing the disease. Methods A qualitative grounded theory approach was used that employed focus group interviews with participants, including clinicians and stroke survivors, to develop a holistic understanding of primary and secondary stroke care services and the experiences of those accessing them. Results Clinicians believed they were not optimally equipped to manage diabetes as a condition. They believed more emphasis should be placed on self-management, which would be better managed by lifestyle changes than medication alone. Conversely, stroke survivors with diabetes experienced an additional burden associated with the diagnoses but relied on clinicians to manage their diabetes and believed the clinicians were failing if they were unwilling or unable to achieve this. Discussion The research highlights the tensions between stroke survivors and healthcare professionals. Stroke survivors relied on the healthcare teams to provide the optimal treatment when they had recently undergone a significant health event where they had experienced a stroke and received a diabetes diagnosis. However, the healthcare teams, while recognizing the importance of a holistic and comprehensive treatment package, struggled to provide it due to resource limitations. To optimize post-stroke diabetes self-management education, a strategic framework that prioritizes patient empowerment and interdisciplinary collaboration is paramount. Tailoring educational interventions to align with individual patient profiles—considering their unique health status, personal preferences, and cultural context—is essential for fostering self-efficacy. Such a strategy not only empowers patients to take an active role in managing their diabetes post-stroke but also contributes to superior health outcomes and an elevated standard of living.